Infection control of COVID-19, how consistent is the medical perspective and the Islamic perspective? - Mohamed, Mossad Abdelhak Shaban; Rosternberghe, Hans; Ramli, Noraida; Ibrahim, Roshidah; Mossad, Manar (Universiti Sains Islam Malaysia Publication type: Print & Electronic, 2020)
In the era of the current COVID-19 pandemic, the infection control becomes of utmost importance at individual and global levels to control the crisis. There is scarce data on the extent of consistency between the Islamic regulations and the medical recommendation. These include travel bans and quarantine, social distancing, isolation, personal responsibility, combining interest of the individual and the benefit of society and following and assisting the state officials. We aimed in this work to highlight the reliability of the Islamic principles to infection control during the pandemic with the overall medical recommendations.